Embracing the complexity of policy processes in sanitation: Insights from India. (11th December 2017) - Hueso, Andrés; Boni, Alejandra; Fernández‐Baldor, Álvaro
Abstract: Different stakeholders tried participatory approaches to boost progress in rural sanitation in India. The policy processes around these experiences, despite shaping their outcomes, remain a knowledge gap this article addresses. Evidence shows that the interests of the actors involved resulted in the national campaign being focused on construction. Therefore, participatory approaches could only be successfully introduced through networks with political champions at their centre. Moreover, political dynamics determined the success of the different introduction strategies. A better understanding of these policy processes, using analytical frameworks such as the one we propose, will lead to smarter influencing strategies in the sanitation sector.